Effect of Modulation of the Inlet Velocity and Equivalence Ratio Gradients on the Stabilization of Stratified Axisymmetric Bluff-Body Flames - G. Paterakis; P. Koutmos (Journal of Combustion)
An investigation of ultralean stratified, disk stabilized, propane flames operated with acoustic modulation of the inlet velocity and fuel-air mixture profiles is presented. Transverse acoustic forcing was applied to the air, upstream of a double-cavity premixer section, formed along three concentric disks, which fueled the stabilization region with a radial mixture gradient. Measurements and supporting Large Eddy Simulations with a nine-step mechanism for propane combustion were performed to evaluate variations in the ultralean flame characteristics under forced and unforced conditions. The effects of forcing on the heat release profiles and on the interaction of the toroidal flame with the recirculation region are examined and discussed. The impact of the acoustic excitation of inlet conditions on the local extinction behavior is, also, assessed by monitoring a local stability criterion and by analyzing phase-resolved chemiluminescence images.